Teknologi pengambilan lemak dari sisa fleshing - Sutyasmi, Sri; Sunaryo, Ignatius (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2006)
The aim of this research was to recover the fat from fleshing in order it could be useful for many kinds of industries such as soap, oil/grease for tanning manufactures, etc. There are some systems to recover the fat from fleshings, those are heat systems (cooking, steaming, smoking) and extrac system using solvent (hexan, CCl4, alcohol, etc). Over all of the systems cooking and steaming are the most simply system to recover the fat. By cooking, smoking, and steaming from 5 kg fleshing with the time variation of 15,30, 45 and 60 minutes could produce fat with the quantity of which varied from 0,220 â 0,425 kg. The highest quantity of fat, produced byÂ heating system in 60 minutes could be gained by steaming, but the quality of it was low.Â The quantity of fat produced by extract system using hexan, CCl4, andÂ alcohol as solvents with the time variation of 3,4 and 5 hours were varied from 5,21 % to 10,20 % of dried weight. The highest quantity of fat gained by extract system was found by using hexan solvent. Fat from fleshing should be sulphated prior for substantial application. The economical evaluation shows that the basic price of 1 kg of fat was Rp. 1.250,- whereas the basic price of 1 kg of sulphated fat was Rp. 3.200,- Â Keywords ; fleshing, grease, recovery Â ABSTRAK Â Tujuan dari penelitian ini adalah untuk memisahkan lemak dari fleshing agar bias digunakan untuk berbagai keperluan industri seperti sabun, peminyakan kulit dan sebagainya. Pengambilan lemak dari sisa fleshing ini ada beberapa cara yaitu cara pemanasan (rebus, kukus dan steam) dan cara ekstraksi menggunakan pelarut (hexan, CCl4, alcohol dll). Setiap 5 kg sisa fleshing yang direbus, dikukus dan ataupun menggunakan steam, dengan variasi waktu 15, 30, 45 dan 60 menit dapat menghasilkan lemak berkisar antara 0,220 â 0,425 kg. Hasil lemak tertinggi dari cara pemanasan ini diperoleh dari cara steam dengan waktu 60 menit namun kwalitas lemak yang diperoleh tidak baik. Pengambilan lemak secara ekstraksi dengan menggunakan pelarut hexan, CCl4 dan alcohol dengan variasi waktu 3 jam, 4 jam dan 5 jam dan lemak yang diperoleh berkisar antara 5,21% - 10,20 %. Hasil lemak tertinggi diperoleh dari cara ekstraksi menggunakan pelarut hexan. Agar lemak dapat dimanfaatkan untuk berbagai keperluan, maka lemak perlu disulfonasi. Hasil perhitungan ekonomi harga pokok 1 kg lemak adalah Rp.1.250,- sedangkan harga pokok 1 kg minyak sulfonasi adalah Rp. 3.200,-Â Kata kunci : fleshing, lemak, pengambilan